Website Based Patient Clinical Data Information Filling and Registration System - Agung Suryadi; Ts Arvindi Balakrishnan (Global Health Science Group, 2023)
Patient registration is very important in health care services. Various strategies have been implemented in optimizing services, one of which is by developing a web-based outpatient registration system. The purpose of this study is to build a computer-based web-based outpatient registration information system. The type of research used is descriptive by means of a survey, the variables used are flow and outpatient registration procedures, patient data, doctor data, payment method data, polyclinic data. The object of this research is the Outpatient Registration Officer. The instruments used were interview guidelines and observation guidelines, as well as using the Development Life Cycle (SDLC) system development system. Using PHP, HTML, CSS and Java script programming languages, with MySQL database. This information system can make it easier for patients to register themselves without having to go to the hospital first.